2012
DOI: 10.1590/s1676-06032012000300017
|View full text |Cite
|
Sign up to set email alerts
|

Lagartos de áreas de cerrado na Reserva Biológica Unilavras-Boqueirão, Ingaí, Sul de Minas Gerais, Brasil

Abstract: Studies with emphasis on assessment and quantification of species biological diversity should be recognized as important tools in the process of knowledge, especially where basic data are scarce. This study was conducted at the Reserva Biológica Unilavras-Boqueirão (21° 20' 47" S and 44° 59' 27" W) inserted in the Cerrado, Ingaí municipality, southern Minas Gerais, southeastern Brazil. We aimed to characterize and understand local lizard species. Sampling occurred between June 2008 and February 2010 in weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The regional lizard fauna is composed predominantly of species with wide distribution and endemic species from the Atlantic Rainforest biomes. Despite the existence of records of Heterodactylus imbricatus (Novelli et al 2011) and Urostrophus vautieri (Novelli et al 2012) in Cerrado, we still consider these species as endemic to the Atlantic Forest biome, since these records are from riparian forests in marginal areas of this biome. Considering this, there are five species endemic from Atlantic Rainforest in the Serra do Ouro Branco.…”
Section: Discussionmentioning
confidence: 91%
“…The regional lizard fauna is composed predominantly of species with wide distribution and endemic species from the Atlantic Rainforest biomes. Despite the existence of records of Heterodactylus imbricatus (Novelli et al 2011) and Urostrophus vautieri (Novelli et al 2012) in Cerrado, we still consider these species as endemic to the Atlantic Forest biome, since these records are from riparian forests in marginal areas of this biome. Considering this, there are five species endemic from Atlantic Rainforest in the Serra do Ouro Branco.…”
Section: Discussionmentioning
confidence: 91%
“…However, Novelli et al (2011Novelli et al ( , 2012 recorded H. imbricatus in gallery forest of this biome in the municipality of Ingaí in southern Minas Gerais. In the study by Cruz et al (2014) in the Ouro Branco mountains, the species E. gaudichaudii was recorded, while H. imbricatus was recorded in riparian forest.…”
Section: Discussionmentioning
confidence: 95%
“…Through expansion of reptiles inventories (Cruz et al 2014;Lucas et al 2016;Novelli et al 2012;São Pedro & Pires 2009;Silveira et al 2010), it has been found that there is high diversity of reptiles in the Cerrado biome (Brites & Baub 1988;Recoder & Nogueira 2007). These studies have even shown that the distribution of some species is increasing (Santos et al 2009;Novelli et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2007; Novelli et al . 2012), mainly due to the presence of several specialist species (Vitt 1991; Vitt et al . 2007; Nogueira et al .…”
Section: Introductionmentioning
confidence: 99%